Looking into black eyes and feel the embarrassment. A Selected and Selective Reading of The Africana Bible - Snyman, Gerrie 19XX- (Old Testament essays, 2011)
Employing a hermeneutics of vulnerability to unmask privileged positions, this article intends to provide a reading from a white perspective of The Africana Bible. Reading Israel's Scriptures from Africa and the African Diaspora. The hypothesis is that the book constitutes an exercise in reading the Old Testament/Hebrew Bible/ First Testament in terms of a coloniality of being. Firstly, the socio-political relevance of an open discussion of racism will be illustrated by a recent example of a dispute that originated within racialized South African public discourse on the issue of white supremacy. Based on this example, the discussion will proceed to arguments regarding decoloniality after which a reading of selected chapters of The Africana Bible will be presented.